Administration of bali arabica (Coffea arabica) coffee extracts decreases abdominal fat and body weight in obese wistar rats (Rattus norvegicus) - Fanny Rustandi; I Gusti Made Aman; Gde Ngurah Indraguna Pinatih (Fakultas Kedokteran Universitas Udayana, 2019)
Introduction: The amount of obesity in the world in 2016 tripled compared to 1975 based on data from the World Health Organization (WHO). Previous research has shown that coffee has the potential to reduce weight and heavy abdominal fat. But there has been no research on extracts of Balinese arabica coffee beans. The purpose of this study was to prove that extracts of Balinese Arabica coffee beans can reduce weight and weight of abdominal fat in obese wistar male rats. Methods: This research is a study using Post-test only Control Group Design. The research subjects were 36 male white rats wistar (Rattus norvegicus) strain, healthy, aged 3-4 months and obese (Lee index> 0.3) divided into two groups, each amounting to 18 rats. The control group (P0) was the one who received placebo and the treatment group (P1) was given bali coffee bean extract 800mg / kgBW / day for 28 days. The variables observed were body weight, abdominal subcutaneous fat weight (BLS), and weight of visceral abdominal fat (BLV). In addition, the remaining food is measured every day. Results: The results showed the mean body weight P0 302.33 ± 6.22gram, P1 286.88 ± 4.85 gram (p <0.005). The mean BLS P0 was 0.61 ± 0.07 grams and P1 was 0.41 ± 0.08 grams (p <0.005). The mean BLV P0 5.55 ± 0.90 gram and P1 4.58 ± 0.60 gram (p <0.005). The mean feed remaining from the control group was 4.081 ± 0.57 grams and from the treatment group 6.07 ± 0.64 grams (p <0.005). Conclusion: Based on the above data it can be concluded that the administration of Bali coffee bean extract can reduce weight, weight of abdominal subcutaneous fat and heavy abdominal visceral fat in male wistar rats with obesity. In addition, it is suspected that extract of Bali coffee beans also reduces the amount of food intake.